PHONETIC VARIATION IN DIFFERENT ENGLISH ACCENTS - Gafurjanova Ferangiz (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Phonetic variation is one of the most distinctive features of the English language, reflecting both linguistic evolution and cultural diversity. This article examines the phenomenon of phonetic variation across different English accents, focusing on the factors that influence pronunciation differences and their sociolinguistic implications. The study analyzes vowel quality, consonant articulation, and suprasegmental features such as stress and intonation. The findings indicate that while English accents differ significantly across regions, they  maintain a core phonological system that ensures mutual  intelligibility.  These  variations  illustrate  how  English  adapts  to  social, geographical, and historical contexts, making it a global yet locally distinct language.